Mapping time : keynote :Powerpoint - Kraak, M.J. (University of Twente, 2020)
This lecture presents: Working environment for visual exploration; Temporal actions; Interactive animation; Worldtime and display time; Summer and winter time; The network or the objects; Current solutions: representation and design.